EFFECTIVENESS OF CITRONELLA (CYMBOPOGON NARDUS) EXTRACT IN CONTROLLING PESTS AND DISEASES ON SURI 4 SORGHUM IN THE DRYLANDS OF NORTH CENTRAL TIMOR - Nikolas Nik; Aloysius Rusae (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2025)
Sorghum variety Suri 4 is an alternative food crop known for its adaptability to dryland conditions. However, its productivity is often constrained by pest and disease infestations. Lemongrass (Cymbopogon nardus) contains natural active compounds with potential as an environmentally friendly botanical pesticide. This study aims to examine the effects of various concentrations and application frequencies of lemongrass leaf extract on the growth, yield, and levels of pest and disease incidence in Suri 4 sorghum. The research was conducted in Lapeom Village, Insana Barat Subdistrict, North Central Timor Regency, using a two-factor Randomized Block Design (RBD). The first factor was extract concentration (0, 50, 75, and 100 g/l), and the second was spraying frequency (3, 5, and 7 times), resulting in 36 experimental units. Data were analyzed using analysis of variance (ANOVA), followed by Duncan’s Multiple Range Test (DMRT) at a 5% significance level. The results indicated that the application of 100 g/l lemongrass extract combined with seven sprayings yielded the best performance in enhancing plant growth and sorghum yield, while effectively reducing aphid infestation and leaf spot disease incidence. Thus, lemongrass extract is recommended as a biological control strategy in sorghum cultivation under dryland conditions.